Potencial anti-hiperglicêmico do extrato de Connarus suberosus planch. em modelo experimental de diabetes mellitus induzido por estreptozotocina - Picolotto, Aline (My University, 2025)
Diabetes Mellitus (DM) is one of the most prevalent chronic diseases of the 21st century, currently affecting approximately 537 million adults worldwide, with projections reaching 780 million cases by 2045. In recent years, the search for therapeutic alternatives that promote glycemic control and reduce oxidative damage associated with DM has intensified. In this context, the investigation of bioactive compounds derived from plants has emerged as a promising strategy for managing and preventing complications related to this disease. Among plant species from various biomes with anti-hyperglycemic potential, the Connaraceae family stands out. Our research on this family began in 2015 with studies on Rourea cuspidata. Since then, we have conducted investigations on four other species from different Brazilian biomes, with particular emphasis on Connarus suberosus, a plant native to the cerrado, which has shown promising results. This study aimed primarily to evaluate the anti-hyperglycemic activity of the aqueous extract of C. suberosus in streptozotocin-induced diabetic rats. The results demonstrated that treatment with the extract over 28 days promoted significant antihyperglycemic activity and provided protective effects on renal parameters, maintaining urea and creatinine levels similar to those of non-diabetic control animals. Additionally, the extract showed benefits in lipid profile, oxidative stress, and hepatic complications, attributed to its antioxidant and anti-inflammatory properties derived from its bioactive compounds. This work also includes a comprehensive review of species in the Connaraceae family, published in 2021 in the Journal of thnopharmacology, and a patent filed with the INPI (registration BR 102021016273-2-A2), which indicates the use of extracts from this family for DM control. These findings highlight the potential of C. suberosus as a promising therapeutic resource for the treatment of Diabetes Mellitus. [resumo fornecido pelo autor]
O Diabetes Mellitus (DM) é uma das doenças crônicas mais prevalentes do século XXI, afetando aproximadamente 537 milhões de adultos em todo o mundo, com projeções de alcançar 780 milhões de casos até 2045. A busca por alternativas terapêuticas que promovam o controle glicêmico e reduzam os danos oxidativos associados ao DM tem se intensificado nos últimos anos. Nesse contexto, a investigação de compostos bioativos derivados de plantas tem se mostrado uma estratégia promissora para o manejo e a prevenção de complicações decorrentes da doença. Dentre as espécies vegetais presentes em diferentes biomas do mundo, com potencial anti-hiperglicêmico, destaca-se a família Connaraceae, a qual, temos um histórico de trabalhos anteriores, iniciando em 2015 com a Rourea cuspidata. Desde então, foram conduzidos trabalhos com outras quatro espécies, provenientes de vários biomas brasileiros, com destaque para Connarus suberosus, uma planta originária do cerrado, que demonstrou resultados promissores. Este trabalho teve como principal objetivo avaliar a atividade anti-hiperglicêmica do extrato aquoso de C. suberosus em ratos diabéticos induzidos por estreptozotocina. Os resultados demonstraram que o tratamento com o extrato, ao longo de 28 dias, promoveu significativa atividade anti-hiperglicêmica, além de efeitos protetores nos parâmetros renais, mantendo níveis de ureia e creatinina semelhantes aos de animais não diabéticos. Adicionalmente, o extrato apresentou benefícios no perfil lipídico, no estresse oxidativo e nas complicações hepáticas, atribuídos às suas propriedades antioxidantes e antiinflamatórias de seus compostos bioativos. Este trabalho também inclui uma revisão abrangente sobre as espécies da família Connaraceae, publicada em 2021 na Journal of Ethnopharmacology, e uma patente depositada no INPI (registro BR 102021016273-2-A2), que indica o uso de extratos dessa família no controle do DM. Os achados reforçam o potencial de C. suberosus como um recurso terapêutico promissor para o tratamento do Diabetes Mellitus. [resumo fornecido pelo autor]
Keywords: Diabetes; Hiperglicemia; Flavonóides; Diabetes; Hyperglycemia; Flavonoids